Is it possible a new definition of metabolic syndrome in childhood? - Martino, F; Pannarale, G; Puddu, P E; Colantoni, C; Zanoni, C; Martino, E; Torromeo, C; Paravati, V; Perla, F M; Barillà, F (European review for medical and pharmacological sciences, 2015)
To investigate whether a group of Italian children and adolescents who were diagnosed to have metabolic syndrome (MS) according to a new ethnic age and gender specific definition had, in comparison with a control group, other signs and metabolic risk factors which are commonly associated with MS. The cross-sectional study population included 300 subjects (51% boys, age range 6-14 years), who were divided into 2 groups according to the presence of MS, diagnosed on the basis of 3/5 factors derived from the age and gender specific quantile distribution of MS components in a large regional Italian population survey (Calabrian Sierras Community Study, CSCS). In all subjects the following data were collected: anthropometric measures, blood pressure, liver function, C-reactive protein (hsCRP), uric acid blood levels, lipid and glucose profile. Triglycerides/HDL-cholesterol (TG/HDL-C) ratio was calculated. There were 38 subjects (13%) with MS, who had higher indices of growth and fat distribution and higher blood levels of uric acid, alanine aminotransferase and gamma-glutamyltransferase. TG/HDL ratio was higher (median 3.11 vs. 1.14, p = 0.00001) in MS subjects who had lower apolipoprotein A and higher apolipoprotein B and non-HDL-C levels. hsCRP was not different between groups. Our ethnic age and gender specific definition of MS in Italian children and adolescents was able to identify in a youth group different cardiometabolic risk factors related to insulin resistance, endothelial damage and nonalcoholic fatty liver disease, which are commonly associated with MS diagnosis.